Pengaruh Model Pembelajaran AIR Terhadap Peningkatan Keterampilan Menyimak Bahasa Arab Siswa SMPU Karangsawo Lamongan - Abdul Taufik Bangga; Nurul Fahmi (Annusfy : Journal of Multidisciplinary Research, 2026)
The purpose of this study is to apply the AIR learning model and determine its effect on improving Arabic listening skills of students at Karangsawo Lamongan Junior High School. Using a quantitative quasi-experimental design approach. Data collection through observation, documentation, pretest and posttest. Data analysis using the t-test. The results of this study indicate that the application of the AIR model has a significant effect on improving students' listening skills. This is shown through the results of the t-test with a calculated t-value for the experimental group of 10.73, a t-table value at a significance level of 0.05 is 1.721 and at a level of 0.01 is 2.518. Because the calculated t-value is greater than both t-table values ​​(10.73> 1.721 and 10.73> 2.518), it is known that the null hypothesis (H₀) is rejected and the alternative hypothesis (Ha) is accepted